Epidemiology of Omsk Haemorragic Fever - N. V. Rudakov; V. K. Yastrebov; V. V. Yakimenko (Эпидемиология и вакцинопрофилактика, 2015)
The main aspects of epidemiology and epizootology of omsk haemorrhagic fever (OHF) were analysed. Described: the discovery of virus OHF (1947), the first outbreak of new diseases in districts of Omsk region; comprehensive work for decryption the etiology of OHF of specialists from Omsk and Moscow institutes. In the long-term dynamics of activity of natural foci of OHF stand out 4 periods, what different intensity of epidemic and epizootic processes. The main reservoir of the virus OHF in natural foci and the source of human infection is muskrat. In maintaining populations of the virus is of some significance change of hosts (metaxenosis). Established independent position of the virus OHF in group Flaviviruses of mammals, transmitted by ticks. There are two genovariants of virus OHF.